Trends of the main bibliometric indicators of Anais Brasileiros de Dermatologia (2010-2019) - Miot, Helio Amante [UNESP]; Ianhez, Mayra; Ramos, Paulo Muller [UNESP] (Elsevier B.V., 2021)
Background: The Anais Brasileiros de Dermatologia (Anais Brasileiros de Dermatologia) is the official journal of the Brazilian Society of Dermatology, which has been published since 1925, with free, bilingual access. There are several bibliometric indicators that estimate aspects of a journal's scientific influence. Its analysis, based especially on the evolutionary trend, allows identifying the journal's strengths and weaknesses, in addition to guiding editorial policies. Objectives: To evaluate the trends of the main bibliometric indicators of Anais Brasileiros de Dermatologia, in the decade of 2010-2019. Methods: Methodological study that proposed the analysis of bibliometric indicators published by Journal Citation Reports, SCImago, and Scopus, for the journal Anais Brasileiros de Dermatologia, from 2010 to 2019. The following aspects were evaluated: Impact factor, Immediacy index, SJR (SCImago), in addition to the number of citations, citable items, Cite Score, percentage of external citations, percentage of cited articles, percentage of citable articles, and the article influence score. Results: There was an increase in the main bibliometric indicators in the last decade: impact factor (0.337 to 1.121), immediacy index (0.054 to 0.204),Eigenfactor (0.00025 to 0.00394), SJR (0.176 to 0.453). The percentage of external citations (48.4% to 94.1%) and cited articles (24.7% to 51.4%) also increased. The increase in the impact factors of Anais Brasileiros de Dermatologia in the period was more significant than that of the dermatology journals (1,667 to 2,118) and the Brazilian journals (1,247 to 1,408), indexed in the Journal Citation Reports. Study limitations: Failure in the classification and registration of the databases. Conclusions: There has been a consistent increase in the scientific influence of Anais Brasileiros de Dermatologia in the last decade. (c) 2021 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Bibliometrics; Impact factor; Journal article